A search in Asia for a new theory of music - Buenconsejo, José, S. (Philippines University of the Philippines, 2003)
Collected papers from 'A Search in Asia for a New Theory of Music', a symposium organized by The University of the Philippines Center for Ethnomusicology at the 7th International Conference of the Asia Pacific Society for Ethnomusicology (APSE), held at the University of the Philippines and the Cultural Center of the Philippines, February 17-23, 2002. Edited by Jose S. Buenconsejo. Introduction by Jose Maceda.